Potencialidades e desafios da Rede de Atenção à Saúde do município de Farroupilha - Mansan, Janaína Molon (Universidade do Vale do Rio dos Sinos, 2017)
The Health Care Networks consist in an articulation method among the services, which through technical, logistical and management support aim the integrality in the care provided to the users. This research seeks to verify how the Health Care Networks articulate in the city of Farroupilha, located in the northeast region of the State of Rio Grande do Sul. Objective: present a proposal of a Permanent Educational Program in Health for the city of Farroupilha aiming the strengthening and activation of the Health Care Networks. Method: the components of the research agreed to the Formation Quadrilateral, comprehending the thematic axes of Social Control - Attention - Management. The axis Formation was not contemplated, once there is no educational/training institution in the city. Semi-structured interviews were realized firstly with the users (in Social Control) and, past the analysis of the mentioned data, a new instrument for information gathering was developed to be applied among the professionals and managers (Attention/Management). The research counted with the participation of nine users, three professionals and two managers, totalizing fourteen participants. The thematic analysis was deployed for the results’ analysis, from which two categories emerged. Result and discussion: the first category concerns to the potentialities and challenges of the network related to the attention to health in the city, having as subcategories the participation of the Social Control and the attendance at the Health Care Networks. The second category analysed the communication within the Health Care Networks with their respective subcategories: potentialities and challenges in the system of reference and counter-reference; communication among the Attention/Management/Social Control; discharge orientation and electronic prompt-book. Final Considerations: the results display a lack of knowledge from the users about the functioning of the city’s network and an absence of communication between the professionals and services. Intervention Proposal: under these circumstances, the proposal of this study was elaborated, which comprehended the development of a Permanent Educational Program for the professionals and the production of an illustrated educational primer to assist in the orientation of the users and new professionals.
Keywords: Redes de atenção à saúde; Quadrilátero da formação; Educação permanente; Health care networks; Formation quadrilateral; Permanent education; ACCNPQ::Ciências da Saúde::Enfermagem